Sex-specific survival in advanced metastatic melanoma: a DeCOG study on 2032 patients of the multicenter prospective skin cancer registry ADOREG - Leven, Anna-Sophia; Peters, Triinu; Rajcsanyi, Luisa Sophie; Weichenthal, Michael; Mohr, Peter; Meier, Friedegund; von Wasielewski, Imke; Gutzmer, Ralf; Utikal, Jochen; Terheyden, Patrick; Herbst, Rudolf; Haferkamp, Sebastian; et al. (European journal of cancer, 2025)
Background - Females and males differ in their innate and acquired immune responses. Thus, it is hypothesized that the efficacy of anti-tumor immunotherapies may differ by sex. This study aimed to investigate sex-specific survival differences upon different therapy types in metastatic melanoma. - Patients and Methods - Patients with unresectable metastatic melanoma (stage IV, AJCCv8) of the skin or unknown primary, who had received first-line PD-1-based immune checkpoint inhibition (ICI) or BRAF/MEK-directed targeted therapy (TT) were identified from the prospective multicenter DeCOG skin cancer registry ADOREG. Study endpoints were progression-free survival (PFS) and overall survival (OS). - Results - A total of 2032 patients, 1274 males (62.7%) and 758 females (37.3%), received ICI (n=1484) or TT (n=548) between May 2010 and December 2020. At median follow-up of 28.6 months, no significant sex-specific differences in survival could be detected, neither in the total cohort nor by treatment type: PFS (total, p=0.86; ICI, p=0.46; TT, p=0.21), OS (total, p=0.60; ICI, p=0.20; TT, p=0.30). Multivariable Cox regression analyses also did not show a relevant prognostic influence by sex. Subgroup analyses were performed according to ICI therapy type. In n=872 patients treated with PD-1 monotherapy, a survival advantage (PFS, p=0.041; OS, p=0.07) could be detected for males by univariable and multivariable analyses, whereas no sex-specific survival differences were found for n=456 patients who received combination immunotherapy. - Conclusion - No overall sex-specific survival differences were detected for metastatic melanoma patients in the first-line therapy setting. According to subgroup analyses males show a trend towards a survival advantage over females.
Online verfügbar: 29. Juli 2025, Artikelversion: 31. Juli 2025
Gesehen am 29.10.2025